DLP 3D printing and characterization of PEEK-acrylate composite biomaterials for hip-joint implants - Dama, Yogiraj; Jogi, Bhagwan; Pawade, Raju; Pal, Shibam; Gaikwad, Yogesh (Obrabotka metallov - Metal Working and Material Science, 2025)
Introduction. Hip joint replacement is considered the most complex and critically important orthopedic surgical procedure compared to knee and shoulder joint replacements. Over the past few decades, there has been significant advancement in hip joint replacement technology, and various biomaterials have been substantially improved. An increasing number of hip joint replacement surgeries are now successful, assisting individuals in regaining normal daily activity and work capacity comparable to their pre-fracture state. However, the need for revision surgery, specifically for implant replacement, is still observed in active patients several years following the initial operation. This underscores the need to develop durable biomaterials and customized hip joint implants to reduce implant wear and the risk of dislocation. This research study explores a novel PEEK-in-acrylate composite biomaterial with varied weight percentages of PEEK (0 %, 5 %, and 10 %) in an acrylate-based matrix. Tests were conducted to determine its properties, biocompatibility, and 3D printability. Based on the developed material, pins (in accordance with the ASTM standard) were fabricated using 3D printing for subsequent wear rate studies. The potential use of the developed composite materials for hip-joint applications was also thoroughly investigated. The purpose of this study is to develop and investigate a new PEEK in Acrylate composite biomaterial with varied weight percentages of PEEK (0 %, 5 %, and 10 %) in an acrylate-based matrix. The research includes an assessment of the material's properties, biocompatibility, and 3D printability. Using digital light processing (DLP) 3D printing technology at room temperature, pins (in accordance with the ASTM standard) were fabricated. An experimental study of dry sliding wear resistance was conducted on the resulting samples to determine the effect of PEEK weight fraction on the wear rate and frictional performance against an SS 316 steel disk. Scanning electron microscopy (SEM) and Energy-dispersive X-ray spectroscopy (EDS) were used to analyze the surface structure and element distribution within the material. The Methods of Investigation. Digital Light Processing (DLP) 3D Printing technique was used to 3D Print the ASTM pins and Acetabular liner with different weight fraction of PEEK in acrylate. Dry sliding wear tests were carried out using a pin-on-disk tribometer. During testing, the disk rotation speed and the normal load on the pin were varied. The studies were designed to determine the influence of input parameters on the wear rate. A total of nine experiments were conducted for each PEEK weight fraction, with a sliding distance of 4 km per experiment. The load ranged from 20 to 100 N, and the sliding speed varied from 450 to 750 rpm. Surface structure and element distribution were analyzed by Energy-dispersive X-ray spectroscopy (EDS) and Scanning electron microscopy (SEM). Result and Discussion. Current study demonstrates the advantages of varying the weight fraction of PEEK in Acrylate for DLP-fabricated biomaterials. Analysis of the SEM, EDS, and wear testing results indicated that the composite with 10 wt % PEEK in Acrylate exhibited superior microstructural integrity, elemental homogeneity, and significantly improved wear resistance. The 10 wt % PEEK in Acrylate composite, fabricated via DLP 3D printing, is suitable for biomedical implant and healthcare applications
Keywords: 3D printing; Biomaterials; FDM; implant; PLA; print orientation; wear behavior